1992
DOI: 10.3133/ofr92129
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-climatic data network (HCDN); a U.S. Geological Survey streamflow data set for the United States for the study of climate variations, 1874-1988

Abstract: This work has come to fruition under the U.S. Geological Survey (USGS) Global Change Hydrology Program. We would like to acknowledge the many people who have assisted in the development of the Hydro-Climatic Data Network (HCDN).This project was carried out in cooperation with the Office of Surface-Water of the USGS Water Resources Division, which provided technical and logistical support as needed throughout the course of the project. We are especially grateful for the assistance of Ernest F. Hubbard, Jr., Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
234
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(237 citation statements)
references
References 0 publications
0
234
0
1
Order By: Relevance
“…1): (1) the streamflow gauge stations must contain continuous data for at least 50 years (monthly or daily data), (2) have reduced or be completely free from water diversion, reservoir storage, and other anthropogenic regulations, and (3) have irrigated land occupying less than 10% of the draining watersheds. Of the 99 stations that satisfied these criteria, 53 stations were part of the USGS's Hydro-Climatic Data Network (HCDN; Slack and Landwehr, 1992), 43 stations were found to have very minimal to no impact from diversion, regulation or irrigation, and three stations had less than 10% of draining land impacted by irrigation. Areas of the draining watersheds ranged from 61.5 km 2 in the farthest upstream tributaries in Wyoming to 54,708 km 2 of the James River in South Dakota.…”
Section: Datamentioning
confidence: 99%
“…1): (1) the streamflow gauge stations must contain continuous data for at least 50 years (monthly or daily data), (2) have reduced or be completely free from water diversion, reservoir storage, and other anthropogenic regulations, and (3) have irrigated land occupying less than 10% of the draining watersheds. Of the 99 stations that satisfied these criteria, 53 stations were part of the USGS's Hydro-Climatic Data Network (HCDN; Slack and Landwehr, 1992), 43 stations were found to have very minimal to no impact from diversion, regulation or irrigation, and three stations had less than 10% of draining land impacted by irrigation. Areas of the draining watersheds ranged from 61.5 km 2 in the farthest upstream tributaries in Wyoming to 54,708 km 2 of the James River in South Dakota.…”
Section: Datamentioning
confidence: 99%
“…These gauges, which include most of the Hydroclimatic Data Network gauges (50), are relatively unaffected by flow regulation and characterize major ecoregions and river basins (ref. 51; http://water.usgs.gov/nsip/federalgoals.html); therefore, discharge records from these gauges can be used to describe hydrologic changes caused by factors other than flow regulation, e.g., climate change.…”
Section: Selection Of Long-term Streamflow Gaugesmentioning
confidence: 99%
“…Hurst [1951] found that d = H À 0.5 % 0.23 for a variety of geophysical time series. Vogel et al [1998] looked at the Hurst coefficient corresponding to the USGS's Hydroclimatic Data Network (HCDN) data set [Slack and Landwehr, 1992], and found that, given the shortness of the records, the correlation structure could be explained either by LTP or by non-LTP Box-Jenkins ARMA processes. Assuming that the correla- …”
Section: Trend Test Performancementioning
confidence: 99%